2021
DOI: 10.1155/2021/4623850
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Dynamic Enhanced Magnetic Resonance Imaging in the Diagnosis of Hematological Malignancies

Abstract: The use of dynamic enhanced magnetic resonance imaging technology can effectively explore the diagnosis and clinical application of hematological malignancies. This paper selected 60 patients with hematological malignancies from 2015 to 2019; all of whom were diagnosed with hematological malignancies, including 40 men and 20 women, aged between 40 and 77 years. The main clinical manifestations of the patient are hematological malignancies, fever, and other symptoms. We used Siemens 3.0T to perform MRI and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%